Epidemiology and dermatological comorbidity of seborrhoeic dermatitis: population‐based study in 161 269 employees. (1st October 2019) - Zander, N.; Sommer, R.; Schäfer, I.; Reinert, R.; Kirsten, N.; Zyriax, B.‐C.; Maul, J.‐T.; Augustin, M.
Summary: Background: Seborrhoeic dermatitis is a common but epidemiologically poorly researched chronic skin disease. Objectives: To characterize the prevalence and dermatological comorbidity of seborrhoeic dermatitis in Germany. Methods: In the course of voluntary company skin checks, full‐body examinations were carried out in more than 500 companies by experienced dermatologists and documented electronically. Results: In total, 161 269 participants were included (men 55·5%, mean age 43·2 ± 10·9 years). Seborrhoeic dermatitis was identified in 3·2% (men 4·6%, women 1·4%). A significant difference was found between age groups (2·0% in < 35; 3·6% in 35–64; 4·4% ≥ 65 years). The most frequent concomitant skin conditions were: folliculitis [17·0%, 95% confidence interval (CI) 15·9–18·1], onychomycosis (9·1%, 95% CI 8·3–10·0), tinea pedis (7·1%, 95% CI 6·3–7·8), rosacea (4·1%, 95% CI 3·6–4·7), acne (4·0%, 95% CI 3·4–4·5) and psoriasis (2·7%, 95% CI 2·3–3·2). Regression analysis revealed the following relative dermatological comorbidities when controlling for age and sex: folliculitis [odds ratio (OR) 2·1, 95% CI 2·0–2·3], contact dermatitis (OR 1·8, 95% CI 1·1–2·8), intertriginous dermatitis (OR 1·8, 95% CI 1·4–2·2), rosacea (OR 1·6, 95% CI 1·4–1·8), acne (OR 1·4, 95% CI 1·2–1·7), pyoderma (OR 1·4, 95% CI 1·1–1·8), tinea corporis (OR 1·4, 95% CI 1·0–2·0), pityriasis versicolor (OR 1·3, 95% CI 1·0–1·7) and psoriasis (OR 1·2, 95% CI 1·0–1·5). Conclusions: Seborrhoeic dermatitis is a common disease, which is more prevalent in men and older people, and it has an increased rate of dermatological comorbidity. However, absolute differences in the prevalence of comorbidities are small and negligible. Nevertheless, the findings underline the need for integrated, complete dermatological diagnostics and therapy.